BLISS: A Bioorthogonal Dual-Labeling Strategy to Unravel Lignification Dynamics in Plants. Issue 3 (16th March 2017) - Lion, Cedric; Simon, Clémence; Huss, Brigitte; Blervacq, Anne-Sophie; Tirot, Louis; Toybou, Djadidi; Spriet, Corentin; Slomianny, Christian; Guerardel, Yann; Hawkins, Simon; Biot, Christophe
Summary: A better in vivo understanding of lignin formation within plant cell walls will contribute to improving the valorization of plant-derived biomass. Although bioorthogonal chemistry provides a promising platform to study the lignification process, methodologies that simultaneously detect multiple chemical reporters in living organisms are still scarce. Here, we have developed an original bioorthogonal labeling imaging sequential strategy (BLISS) to visualize and analyze the incorporation of both p -hydroxyphenyl (H) and guaiacyl (G) units into lignin in vivo with a combination of strain-promoted and copper-catalyzed azide-alkyne cycloadditions. On our path to BLISS, we designed a new azide-tagged monolignol reporter for H units in metabolic lignin engineering and used it in conjunction with an alkyne-tagged G unit surrogate to study lignification dynamics in flax. Here, we show that BLISS provides precise spatial information on the zones of active lignification and reveals polarization in single-cell lignification dynamics. Graphical Abstract: Highlights: An H unit chemical reporter was created for metabolic lignin engineering BLISS, a bioorthogonal dual-labeling strategy, was developed and applied in vivo BLISS provides precise spatial information on lignification dynamics in plants Cell polarization with regard to zones of active lignification is revealed Abstract : Lion et al. develop a dual metabolic labeling methodology (BLISS) for the study of lignification dynamics in plants. The authors demonstrate that SPAAC and CuAAC can be mutually compatible in vivo, and the method provides precise spatial information on the zones of active lignin biosynthesis.